2007
DOI: 10.1016/j.neuroimage.2006.08.048
|View full text |Cite
|
Sign up to set email alerts
|

A spatial and temporal comparison of hemodynamic signals measured using optical and functional magnetic resonance imaging during activation in the human primary visual cortex

Abstract: Functional near infrared spectro-imaging (fNIRSI) is potentially a very useful technique for obtaining information about the underlying physiology of the blood oxygenation level dependent (BOLD) signal used in functional magnetic resonance imaging (fMRI). In this paper the temporal and spatial statistical characteristics of fNIRSI data are compared to those of simultaneously acquired fMRI data in the human visual cortex during a variable-frequency reversing checkerboard activation paradigm. Changes in the size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
71
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 51 publications
7
71
0
Order By: Relevance
“…<0.1 Hz) resting-state fMRI signal correlates with the delta band spontaneous electric signal recorded from brain [30]. Given that HbO 2 and Hb are correlated with fMRI signal [31], the higher power of HbO 2 and Hb fluctuations recorded from ASD in the present work is in line with the MEG studies. In an effort to improve previous efforts at functional imaging diagnostic classification, we constructed a SVM model using salient components of our findings including bilateral correlation coefficients of HbO 2 , HbO 2 power and Hb power to differentiate between ASD and TD.…”
Section: Discussionsupporting
confidence: 84%
“…<0.1 Hz) resting-state fMRI signal correlates with the delta band spontaneous electric signal recorded from brain [30]. Given that HbO 2 and Hb are correlated with fMRI signal [31], the higher power of HbO 2 and Hb fluctuations recorded from ASD in the present work is in line with the MEG studies. In an effort to improve previous efforts at functional imaging diagnostic classification, we constructed a SVM model using salient components of our findings including bilateral correlation coefficients of HbO 2 , HbO 2 power and Hb power to differentiate between ASD and TD.…”
Section: Discussionsupporting
confidence: 84%
“…Greatest levels of activation, and therefore increase in HbO, as a result of visual stimuli, have been observed from optodes that overlie the primary visual cortex [3][4][5] with a greater response typically seen in the left hemisphere. [6][7][8] The amount of activation measured tends to decrease with radial distance from this location. Using the International 10-20 System of Electrode Placement, 9 Wijeakumar et al 7 showed that the largest changes in hemoglobin concentration occurred at O1 and O2 as well as locations vertically between O1, O2, PO3, and PO4.…”
Section: Introductionmentioning
confidence: 90%
“…[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] It can provide both topographic 15,16,[34][35][36] and tomographic 14,37 brain images. SpeciÂŻcally, fNIRS monitors regional cerebral blood°ow (rCBF) variations by measuring, at wavelengths between 700 nm and 1000 nm, the near-infrared-lightabsorption changes caused by concentration variations of HbO and HbR, the two primary absorbing chromophores in brain capillary blood.…”
Section: Introductionmentioning
confidence: 99%